Heterogeneous Motives in the Trust Game: A Tale of Two Roles - Antonio M. Espín; Filippos Exadaktylos; Levent Neyse (Frontiers in Psychology, 2016)
Trustful and trustworthy behaviors have important externalities for the society. But what exactly drives people to behave in a trustful and trustworthy manner? Building on research suggesting that individuals' social preferences might be a common factor informing both behaviors, we study the impact of a set of different motives on individuals' choices in a dual-role Trust Game (TG). We employ data from a large-scale representative experiment (N = 774), where all subjects played both roles of a binary TG with real monetary incentives. Subjects' social motives were inferred using their decisions in a Dictator Game and a dual-role Ultimatum Game. Next to self-interest and strategic motives we consider preferences for altruism, spitefulness, egalitarianism, and efficiency. We demonstrate that there exists considerable heterogeneity in motives in the TG. Most importantly, among individuals who choose to trust as trustors, social motives can differ dramatically as there is a non-negligible proportion of them who seem to act out of (strategic) self-interest whereas others are driven more by efficiency considerations. Subjects' elicited trustworthiness, however, can be used to infer such motivations: while the former are not trustworthy as trustees, the latter are. We discuss that research on trust can benefit from adding the second player's choice in TG designs.
Keywords: 330; trust game; dictator game; ultimatum game; social preferences; self-interest